Mechanistic study of the complex photooxidation of allyl methyl sulfide (AMS): reaction paths and products of addition under different atmospheric conditions - Ladino Cardona, Miyer Alejandro (2023)
The addition mechanism of the OH-initiated oxidation of allyl methyl sulfide (AMS) under atmospheric conditions was studied theoretically using both density functional theory (DFT) and the SVECV-f12 composite method. We found that the addition does not occur directly but rather through a pre-reactive complex that serves as a previous stage for addition at both the C1 and C2 positions. However, based on thermodynamics the addition at C2 possibly occurs by branching of the C1 addition mechanism. Once the addition proceeds, the reaction with O2 under atmospheric conditions produces RO2 radicals that can decompose in multiple ways. Complex mechanisms of intramolecular rearrangement and decomposition both in the absence and presence of NOx have been examined. The thermodynamically most favourable decomposition paths produce 2-hydroxy-acetaldehyde, 2-methyl-thio-acetaldehyde, formaldehyde, and the methyl thiomethyl peroxy (MSP) intermediate. This latter species is proposed as the main source of sulfur dioxide (SO2), which is the product found in the highest yield during the experimental determinations.